A “philosophical molecule,” hydrogen may overcome senescence and intractable diseases - Hirano, Shin-ichi (Med Gas Res, 2020)
It has been revealed that the cause of senescence and diseases is associated with the reactive oxygen species “hydroxyl radicals” (·OH). Senescence and diseases may be overcome as long as we can scavenge •OH mostly produced in mitochondria. It is one and only one “molecular hydrogen” (H(2)) that can both penetrate into the mitochondria and scavenge the •OH. The H(2) in the body can function in disease prevention and recovery. H(2) gas is explosive so that a safe hydrogen inhaler has to be developed for home use. We would like to advocate the great use of H(2).